Emergency duodenopancreatectomy for blunt abdominal trauma. Contribution of a new case and review of the bibliography - Ribero Lavié, Gustavo; Cartazzo, José María; de Mello, Washington; Sauto, Sergio (Cirugía del Uruguay, 1999)
The authors present a new case of severe trauma of the pancreas, due to closed abdominal trauma which required urgent excision surgery. They present the clinical case, operative findings and surgical treatment, which consisted of urgent atypica/ duodenopancreatectomy. Discussion is centered on the lesiona/ type of pancreatic trauma and its therapeutica/ alternatives. They point out the good postoperative evolution and the low frequency of this type of trauma which explains the scarce national and international casuistry. They a/so present comparative series as regards frequency and morbimortality.